1988
DOI: 10.1002/ange.19881001111
|View full text |Cite
|
Sign up to set email alerts
|

Organobimetallkomplexe aus Mg und Pd als Zwischenstufen bei der Bildung von amorphem MgPdCxHy aus Mg(C2H5)2 und [Pd(η3‐C3H5)2]

Abstract: NMR‐spektroskopisch bei tiefer Temperatur identifiziert wurden 1 und 2 als Zwischenstufen der Bildung von amorphem MgPdCxHy 3 au Mg(C2H5)2 und [Pd(η3‐C3H5)2]. Das experimentell bestimmte Produktverhältnis 3: Ethen: Propen: Ethan = 1:2:1:1 konnte durch die Annahme einer weiteren Zwischenstufe, die aus 2 und Mg(C2H5)2 entstehen könnte, plausibel gemacht werden. 3 interessiert als metallorganische Vorstufe für die Abscheidung intermetallischer Verbindungen aus der Gasphase. magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Employing this type of structural framework, local ordering about palladium in MgPdC^H^c an be envisaged (Figure 5b): the first Pd-Mg and Pd-Pd shells at 2.78 A yield a primary mixed Mg/Pd distorted cubic coordination geometry about palladium metal. Additional Pd atoms are located on the xy plane from the central Pd atom at a distance of 3.08 (6), which is reminiscent of the Pd-Pd separation along a and b for Mg0.9Pd1.i.. The observed Pd-C distance, 2.35 (7) A, suggests that carbon is located at the center of the ac face.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Employing this type of structural framework, local ordering about palladium in MgPdC^H^c an be envisaged (Figure 5b): the first Pd-Mg and Pd-Pd shells at 2.78 A yield a primary mixed Mg/Pd distorted cubic coordination geometry about palladium metal. Additional Pd atoms are located on the xy plane from the central Pd atom at a distance of 3.08 (6), which is reminiscent of the Pd-Pd separation along a and b for Mg0.9Pd1.i.. The observed Pd-C distance, 2.35 (7) A, suggests that carbon is located at the center of the ac face.…”
Section: Methodsmentioning
confidence: 87%
“…7H and 13C NMR have demonstrated that the formation of this material proceeds through an organobimetallic intermediate which undergoes elimination of the organic ligands. 6 To define the local structural arrangement about palladium in MgPdCxHy, an X-ray absorption study has been undertaken of this amorphous material as isolated from the reaction solution and of other members of the magnesium-palladium system MgPd and Mgo.gPdu-The EXAFS of metallic palladium and of palladium carbide PdC0.i5 are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MgHT and Mg* found useage as reagents in organic and inorganic syntheses because of their high rea~tivity!~'] They have also been employed for the preparation of intermetallic compounds and their hydrides and carbides via non-metallurgic routes. [42] In the following, we shall review more recent developments in the area of energy storage (for earlier work, see Ref.…”
Section: '~' ]mentioning
confidence: 99%
“…Further developments have led to heterobimetallic reagents that show reactivities distinct from their monometallic components. In particular, different selectivities and improved functional group tolerance in organic transformations as well as modified activities and selectivities in polymerization reactions have been reported. , …”
Section: Introductionmentioning
confidence: 99%